(untitled) (Res Medica, 2013)
Mr. President and Gentlemen, thank you very much for the honour of your invitation, for the courtesy of your presence and for what I am afraid will have to be the patience of your listening. I think it is not inappropriate to gather together some of the connections of our Medical School with the formative years of American medicine, and to present it in these rooms, for it seems that many of the American students to be mentioned were members of this ancient and honourable Society. Important as have been the impulses derived from other sources, kinship, community of language and intercourse have combined to render the influence coming from Scotland the dominant one in the development of American medicine. This is particularly true of the Colonial period and the first half-century of independence of the United States. It has been quite amazing to me to discover so many connections between this School of Medicine and the United States. There does not appear to be one state that has not had some connection in this way, and, indeed, I have had to make a selection and have inevitably omitted many.